About the ideal form of the city Street c. 12th-16th century: misconceptions concerning the 'renaissance' in town-building (Bulletin KNOB, 2003)
In the general historiography of town planning, there is an old and outdated idea which remains to be generally adhered to. This idea, which in essence dates from the 19th century, tells that the straight street and the orthogonal town-plan are typical aspects of 'renaissance town planning', while 'the medieval town' is thought to be an irregular but picturesque ensemble of winding streets and narrow alleys within a tightly fitting town-wall.A very famous passage from Alberti's De re aedificatoria describes the advantages of winding streets as compared to straight streets. This passage is generally commented on in 20th-century historiography as a 'medieval' relic in Alberti's work which is otherwise very much 'renaissance'.In this article this case is taken as a starting point for an interpretation of 12th- to 14th-century written sources on street layout, which show that the traditional interpretations of this passage from Alberti and the general idea of 'medieval town building' as opposed to 'renaissance town building', are wrong: in all the relevant written sources the straight street is clearly preferred above the winding street. So, in fact, Alberti's positive vision on the winding street was more of a new idea than the straight streets he was writing about.The cause of the general misconceptions relating to the straight and the winding street is not the lack of telling sources, but appears to be in the fundament of (art) historical interpretation: the 19th-century system of periodization works as a filter which keeps material that conflicts with the general ideas on (style-)periods, as in this case concerning street layout, from being objectively studied or being studies at all.The concept of a true 'renaissance' in town building is mainly based on the fact that scholars began to write theoretical treatises on architecture and especially town building and fortification in the 15th and 16th centuries. Historians, and even art historians, have taken these treatises rather than the actual towns that were built as their source, and in this way the middle ages versus renaissance dichotomy was confirmed. Thus, the practice of rational town building in the centuries preceding Alberti was, and often still is, looked over or negated.